Feasibility of Using Electrodes with Ultralow Pt Loading in Two-Chamber Microbial Electrolysis Cells - Eunjin Jwa (MDPI AG, 2021)
Decreasing the Pt loading and surface area of the cathode was found to accelerate the hydrogen evolution reaction in microbial electrolysis cells (MEC) at low substrate concentrations. The experimental wire cathode used in this study had a reduced Pt loading of 20 µg Pt/cm2 and only 14% of the surface area of the control disk-type cathode. With the wire cathodes, peak current densities of 33.1 ± 2.3 A/m2 to 30.4 ± 0.5 A/m2 were obtained at substrate concentrations of 0.4 g/L and 1.0 g/L, respectively, which were 5.4 to 6.2 times higher than those obtained with the disk electrode (5.1–5.7 A/m2). The higher cathode overpotentials and higher current densities obtained with the wire electrode compared to those observed with the disk electrode were advantageous for hydrogen recovery, energy recovery efficiencies, and the hydrogen volume produced (8.5 ± 1.2 mL at 0.4 g/L to 23.0 ± 2.2 mL at 1.0 g/L with the wire electrode; 6.8 ± 0.4 mL at 0.4 g/L to 21.8 ± 2.2 mL at 1.0 g/L with the disk electrode). Therefore, the wire electrode, which used only 0.6% of the Pt catalyst amount in typical disk-type electrodes (0.5 mg Pt/cm2), was effective at various substrate concentrations. The results of this study are very promising because the capital cost of the MEC reactors can be greatly reduced if the wire-type electrodes with ultralow Pt loading are utilized in field applications.